HIV/Aids policy - Paul Schutte (Communicare)
In approaching and addressing HIV/Aids, policies should play a major role in orchestrating the country’s attempt to fight the pandemic. Policies on the HIV/Aids issue are mainly formulated at national and provincial levels and there are supposed to be instructive and applicable at local level. Therefore, in this paper, we focus on the communication between provincial and local levels with regard to the HIV/Aids policy in general and the policy documents in particular. Thus, our objectives are the following: to describe a few theories briefly in order to provide a theoretical perspective on policy; to discuss the South African policy on HIV/Aids and the Aids council system in the North-West; to describe the situation at local and provincial levels, with the local level envisaged as the site where policy is implemented; and to provide insights into the way in which communication is working or not working between provincial and local levels, as far as effective policy formulation and implementation are concerned. The findings confirm that there is a large gap between the provincial and local levels. Within the district of Potchefstroom, the knowledge, interpretation and meaning of provincial policy documents are varied and fragmentary. Although a policy is perceived to be a guideline for the Local Aids Council (LAC), most organisations, represented on the LAC, do not experience governmental policy as a guideline for their HIV/Aids programmes and activities.